A comparative study on dust exposure, respiratory symptoms and lung function among farmers and non-farmers - Somaieh Samani; Ramazan Mirzaei; Ali Reza Ansari-Moghaddam (Iranian Journal of Health, Safety and Environment, 2015)
Considering the importance and essence of farmers' health, this study has been conducted with the aim of evaluating the amount of the dust confronting farmers and the farmers' respiratory symptoms and function during the course of wheat collection in 2014 in Zabul villages (Sistan & Balouchestan province, Iran). For this cross sectional study, the dust of the respiratory scope of two groups (farmers and non-farmers) was sampled by PVC filter for 90 minutes with the flow rate of 1.5 lit/min on the basis of NIOSH 0500 method during daily 8 work hours of 5 successive days of manual wheat reaping. Data regarding respiratory symptoms (n=50 rural men over the age of 40) was gathered through interviews and questionnaires, and pulmonary function was measured by Spiro lobe (made in MIR of the US); besides, data analysis was done by SPSS 18, T-Test, Chi-Square, and Logistic regression. The mean dust intensity confronting the farmers was 36.7 mg/m3, and the rate of some breathing complaints namely coughing (P≤0.001), sputum (P≤0.009) and shortness of breath (P≤0.026) became meaningful in the two groups. The average amounts of spirometer parameters of the farmers were less than that of the non-farmers, and the statistical difference of all the parameters except for FEV1/FVC (P=0.06) was meaningful (P≤0.05). The results of the present study indicated that confronting with dust could cause respiratory complaints and decrease spirometer parameters in the farmers.